5S impact on safety climate of manufacturing workers. Issue 3 (4th April 2016) - Srinivasan, Siddarth; Ikuma, Laura Hughes; Shakouri, Mahmoud; Nahmens, Isabelina; Harvey, Craig
Abstract : Purpose: – 5S is a commonly used Lean tool that focusses on creating an organized work environment, but the effects of 5S on safety climate are not as well studied. The purpose of this paper is to determine the impact of a 5S event on safety climate. Design/methodology/approach: – This pre-test post-test study examines the effect of implementing 5S on safety climate of the packaging area of a manufacturing plant. Two groups of employees (case and control groups) completed a safety climate questionnaire (Safety Climate Assessment Toolkit) prior to the 5S event, one month after, and two months after. Findings: – Total safety climate significantly improved for the case group but remained unchanged for the control group over the study period. Specifically, management commitment and involvement dimensions of safety climate improved for the case group. Practical implications: – These results show that two important aspects of safety climate (management commitment and involvement) can be significantly, positively influenced by successful 5S events, which may translate to improved safety overall. Originality/value: – Prior literature on 5S speculates a positive impact of 5S on safety and safety climate, but this assertion is not well supported with empirical evidence. This study provides quantitative measurement of positive safety climate changes that resulted from a successful 5S event. The results provide additional incentive for management to continue 5S and other Lean activities with the possibility of also improving safety.